2016
DOI: 10.1136/annrheumdis-2015-208577
|View full text |Cite
|
Sign up to set email alerts
|

WNT16 antagonises excessive canonical WNT activation and protects cartilage in osteoarthritis

Abstract: ObjectiveBoth excessive and insufficient activation of WNT signalling results in cartilage breakdown and osteoarthritis. WNT16 is upregulated in the articular cartilage following injury and in osteoarthritis. Here, we investigate the function of WNT16 in osteoarthritis and the downstream molecular mechanisms.MethodsOsteoarthritis was induced by destabilisation of the medial meniscus in wild-type and WNT16-deficient mice. Molecular mechanisms and downstream effects were studied in vitro and in vivo in primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
128
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 37 publications
2
128
1
Order By: Relevance
“…However, Nalesso et al 38 showed that while WNT16 was capable of binding Fzd receptors and activating canonical WNT signaling, the degree of activation was significantly lower when compared with the more abundant WNT3A. TOPFlash assays showed that costimulation with both WNT3A and WNT16 resulted in significantly less canonical WNT activation when compared with stimulation using WNT3A alone 38 . Thus, it appears WNT16 acts as a competitive inhibitor of Fzd and acts to ensure the homeostasis of WNT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, Nalesso et al 38 showed that while WNT16 was capable of binding Fzd receptors and activating canonical WNT signaling, the degree of activation was significantly lower when compared with the more abundant WNT3A. TOPFlash assays showed that costimulation with both WNT3A and WNT16 resulted in significantly less canonical WNT activation when compared with stimulation using WNT3A alone 38 . Thus, it appears WNT16 acts as a competitive inhibitor of Fzd and acts to ensure the homeostasis of WNT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A similar function has recently been described for WNT16. Nalesso et al 34. suggest that WNT16 prevents excessive Wnt activation in articular cartilage by acting as a partial agonist of this cascade, thereby competing for receptor binding with a full agonist.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown in zebrafish that wnt16 is downstream of mechanical strains in the developing joint, and controls chondrocyte proliferation and migration. Wnt16 is also linked to hip geometry (74) altered cortical bone thickness (75,76) the response of chondrocytes to injury and to osteoarthritis (77,78).…”
Section: Discussionmentioning
confidence: 99%